On the Road to the New Beginning: History and Utopia in Frank Beyer’s Karbid und Sauerampfer (Carbide and Sorrel) - Lindenberger, Thomas (Cinémas, 2007)
AbstractToday, the film Carbide and Sorrel, by the eminent and recently deceased DEFA director Frank Beyer, is a valuable retrospective look at the construction of the new Germany. Through the story of a worker tossed by his workmates onto the country’s roads in search of carbide in the summer of 1945, this 1963 comedy, made two years after the construction of the Berlin Wall, is a portrait of German society in the grip of the future protagonists of the Cold War. The protagonist’s comic peregrinations between the American and Soviet occupiers are an oblique depiction, reinforced by popular songs of the day, of a utopian existence beyond the dominant political powers.